2009
DOI: 10.4049/jimmunol.0800909
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Apoptotic Speck Protein Containing a Caspase Recruitment Domain (ASC) and NLRP3 in Causing Necrosis and ASC Speck Formation Induced by Porphyromonas gingivalis in Human Cells

Abstract: Periodontal disease is a chronic inflammatory disorder that leads to the destruction of tooth-supporting tissue and affects 10–20 million people in the U.S. alone. The oral pathogen Porphyromonas gingivalis causes inflammatory host response leading to periodontal and other secondary inflammatory diseases. To identify molecular components that control host response to P. gingivalis in humans, roles for the NLR (NBD-LRR) protein, NLRP3 (cryopyrin, NALP3), and its adaptor apoptotic speck protein containing a C-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 44 publications
1
58
0
1
Order By: Relevance
“…Further studies will be required to clarify the exact function played by the NLRP3 inflammasome in the DDR pathway. The anti-proliferative and pro-apoptotic functions of NLRP3 have been reported both here and elsewhere [39,40], but the proposed oncosuppressive activity of the NLRP3 inflammasome now requires confirmation at least in alternative models of inflammation-induced cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies will be required to clarify the exact function played by the NLRP3 inflammasome in the DDR pathway. The anti-proliferative and pro-apoptotic functions of NLRP3 have been reported both here and elsewhere [39,40], but the proposed oncosuppressive activity of the NLRP3 inflammasome now requires confirmation at least in alternative models of inflammation-induced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be required to clarify the exact function played by the NLRP3 inflammasome in the DDR pathway. The anti-proliferative and pro-apoptotic functions of NLRP3 have been reported both here and elsewhere [39,40], but the proposed oncosuppressive activity of the NLRP3 inflammasome now requires confirmation at least in alternative models of inflammation-induced cancer.In summary, we have shown that MSU-induced DNA damage activated the NLRP3 inflammasome in a priming-independent manner, supported oxidative stimulation of DDR, and promoted p53 activation and subsequent cell death. These new roles identified for the NLRP3 inflammasome in suppressing DNA repair and enhancing p53-mediated apoptosis of innate cells will open new avenues of research that clarify the role of NLRP3 in diseases associated with aberrant cell death.…”
mentioning
confidence: 99%
“…NLRC4 contains a CARD that can interact directly with the CARD of procaspase-1 (26); however, ASC is required for some of the responses driven by NLRC4 (27). Macrophages infected with S. Typhimurium or other pathogens exhibit formation of a distinct cytoplasmic ASC focus or speck, which can be visualized under the microscope and is indicative of inflammasome activation (10,28,29). Our laboratory and others have shown that only one ASC speck is formed per cell irrespective of the stimulus used (29)(30)(31)(32).…”
Section: Significancementioning
confidence: 93%
“…ShASC#1, shASC#2, and shASC#1mut THP1 cell lines were generated using retroviral vectors and have been characterized previously (18,23). DUSP10-expressing THP1 cells were generated using the full-length open reading frame cloned into lentiviral vector pLex-JRed (catalogue #OHS4493-98905681; Open Biosystems).…”
Section: Generation Of Cell Lines Isolation Of Mouse Macrophagesmentioning
confidence: 99%
“…It also is silenced in certain cancers (15). Moreover, a caspase-independent type of necrosis induced by high dose Shigella (Ն50 multiplicity of infection) (16), Neisseria gonorrhoeae (17), or Porphyromonas gingivalis (Pg) (18) is ASC-dependent. Asc Ϫ/Ϫ mice exhibit increased susceptibility to Mycobacterium tuberculosis without reduction in IL-1␤, implying additional ASC function that is distinct from cytokine cleavage (19).…”
mentioning
confidence: 99%